Dissesiminated cysticercosis with neurocysticercosis – A rare presentation diagnosed by fine needle aspiration cytology - Singhal, Shipra; Shushmita, Shweta; Sharma, Preeti (International Journal of Research in Medical Sciences, 2019)
Disseminated cysticercosis is a rare presentation of human T. Solium infection in which the parasite disseminates via the blood stream throughout the human body. The various clinical manifestations depend upon the location of the parasitic cyst inside the body. Neurocysticercosis is the most common parasite disease of the central nervous system. Disseminated cysticercosis with neurocysticercosis is a very rare presentation of human cysticercus infection. Here we present such a rare case in which a young man presented with multiple swellings all over the body and a history of seizures. Fine needle aspiration cytology was done and the diagnosis was established.